2017
DOI: 10.1007/s00276-017-1812-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of stylohyoid chain and cervical internal carotid artery detected by 3D angiography

Abstract: 3D-CTA was the most appropriate radiological investigation analyzing and measuring SHC (elongated, larger angle, shorter distances with CICA) and identifying types (duplicated, segmented, complete and fractured) resulting from pressures on the CICA. Our study also revealed the pressure on the artery not only arose from the tip of the SP but could also result from types stretching over the artery wall. In those specimens, there is a higher probability of formation of the stylocarotid syndrome due to the long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…Located between the ICA and the external carotid artery, the distal end of the SP extends inwards, forwards, and downwards (10,11). As shown in our current study, ultrasound could clearly reveal the positional relationship between the SP and blood vessels in the neck.…”
Section: Discussionsupporting
confidence: 70%
“…Located between the ICA and the external carotid artery, the distal end of the SP extends inwards, forwards, and downwards (10,11). As shown in our current study, ultrasound could clearly reveal the positional relationship between the SP and blood vessels in the neck.…”
Section: Discussionsupporting
confidence: 70%
“…Eagle defined a styloid process of 25 mm or longer as being elongated and reported an elongated styloid process was present in 4% of autopsies, among which 4% were symptomatic [ 2 ]. A recent study [ 3 ] reported that the frequency is higher than that reported by Eagle. Currently, many authors define a styloid process that is 30 mm or longer as being elongated [ 4 ].…”
Section: Discussionmentioning
confidence: 79%
“…Spontaneous fracture may occur due to swallowing, yawning, coughing, or sudden laughing [ 10 ]. The underlying causes of traumatic fracture are clear, while those of spontaneous fracture are not; therefore, patients may often be left undiagnosed and the symptoms may be interpreted as “symptoms of unknown cause” or “indefinite complaints.” Recently, many studies have used 3D-CT or 3D-CT angiography when an elongated styloid process is suspected [ 3 , 7 ]. The use of 3D-CT is recommended because it is better than panoramic X-ray in detecting minor fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, yet importantly, it is necessary to emphasize perhaps the most significant factor in the “rise of popularity” of Eagle´s syndrome—a newly described neurological symptomatology possibly associated with the elongated styloid process. It can be a causative factor in the development of internal carotid artery compression [ 2 ], significant compression of the internal jugular vein [ 14 , 15 ], stylocarotid syndrome due to mechanical irritation of the sympathetic plexus in the cervical internal carotid artery [ 16 ] or stroke due to carotid artery dissection [ 17 ]. These recently described neurological morbidities possibly caused by the elongated styloid process have a tendency to spark the interest of many other fellow scientists, a phenomenon known as the “snowball effect”—one study builds upon the previous one.…”
Section: Introductionmentioning
confidence: 99%